2018
DOI: 10.9787/pbb.2018.6.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chromosome-Specific Microsatellite Repeats and Telomere Repeats Based on Low Coverage Whole Genome Sequence Reads in Panax ginseng

Abstract: Repetitive DNA elements are ubiquitous in plant genomes. Although repeats provide relevant information for cytogenetic, evolutionary, and genomic studies, identifying and characterizing their sequence and chromosomal distribution are not always easily achieved through conventional methods. However, a high-throughput identification of genomic repeats can be obtained with short reads from next-generation sequencing data. Here, we identified the telomeric and two chromosome-specific repeats in Panax ginseng using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Owing to recent advances in sequencing technology, the draft genome sequence of P. ginseng has been released by two research groups [37,38]. In addition, we also previously reported the precise transcript sequences of P. ginseng using PacBio single-molecule realtime (SMRT) isoform sequencing (Iso-seq) analysis [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to recent advances in sequencing technology, the draft genome sequence of P. ginseng has been released by two research groups [37,38]. In addition, we also previously reported the precise transcript sequences of P. ginseng using PacBio single-molecule realtime (SMRT) isoform sequencing (Iso-seq) analysis [39].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we demonstrate for the first time that GA promotes storage root secondary growth in P. ginseng. We identified eight putative homologs of the AtGID1 gene in P. ginseng (PgGID1s), based on its draft genome sequence and SMRT Iso-seq data [37][38][39]. Functional genomic analysis of four representative PgGID1s (PgGID1A-D) revealed that the functions of PgGIDs are evolutionarily conserved.…”
Section: Introductionmentioning
confidence: 99%
“…We then determined whether the GA signaling related genes are evolutionarily conserved in P. ginseng genome. To identify GA signaling components, two genomic data obtained from our previous research (Jo et al 2017) and other two groups (Waminal et al 2018;Xu et al 2017) were analyzed. By a blast analysis based on the amino acid sequence of the GA signaling factor of Arabidopsis, it was possible to obtain 14 genes including 4 SLY1s and 10 RGAs in the genome of P. ginseng.…”
Section: Docking Results Of the Ga 3 Interacting With The Pggid1 Proteinsmentioning
confidence: 99%
“…S8c,d ). In addition, we identified telomeric repeats using the same approach 31 ; FISH revealed that all of these sequences are localized to all P. ginseng chromosome termini, with an additional interstitial site detected on one chromosome (Supplementary Fig. S8e ).…”
Section: Resultsmentioning
confidence: 99%